2021
DOI: 10.1186/s40364-021-00278-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the m6A-RNA methyltransferase METTL3 in cancer

Abstract: N6-methyladenosine (m6A) is a prevalent internal RNA modification in higher eukaryotic cells. As the pivotal m6A regulator, RNA methyltransferase-like 3 (METTL3) is responsible for methyl group transfer in the progression of m6A modification. This epigenetic regulation contributes to the structure and functional regulation of RNA and further promotes tumorigenesis and tumor progression. Accumulating evidence has illustrated the pivotal roles of METTL3 in a variety of human cancers. Here, we systemically summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 125 publications
0
15
0
Order By: Relevance
“…For example, methyltransferase-like 3 (METTL3) and METTL14 can form a steady heterodimer complex. They shape the m 6 A methyltransferase complex (MTC) along with their accessory factors Wilms tumor 1-associated protein (WTAP), Vir like m 6 A methyltransferase associated (VIRMA/KIAA1429), RNA binding motif protein (RBM) 15/15b, zinc finger CCCH-Type containing 13 (ZC3H13), and HAKAI [ 5 10 ]. These factors act as m 6 A "writers" and collectively catalyze m 6 A modification.…”
Section: Introductionmentioning
confidence: 99%
“…For example, methyltransferase-like 3 (METTL3) and METTL14 can form a steady heterodimer complex. They shape the m 6 A methyltransferase complex (MTC) along with their accessory factors Wilms tumor 1-associated protein (WTAP), Vir like m 6 A methyltransferase associated (VIRMA/KIAA1429), RNA binding motif protein (RBM) 15/15b, zinc finger CCCH-Type containing 13 (ZC3H13), and HAKAI [ 5 10 ]. These factors act as m 6 A "writers" and collectively catalyze m 6 A modification.…”
Section: Introductionmentioning
confidence: 99%
“…METTL3 is a methyltransferase that can modulate the initiation and progression of various types of cancers [ 27 ]. To determine the function of METTL3 in ESCA, the METTL3 expression pattern in cancer samples and normal samples was analyzed by the Starbase website ( http://starbase.sysu.edu.cn/ ).…”
Section: Resultsmentioning
confidence: 99%
“…METTL3 can function as a regulator for chief oncogenes to facilitate tumorigenesis and tumor progression [ 27 ]. Initially, our findings identified an increased concentration of METTL3 in 162 ESCA samples, ESCA tissues, and cells.…”
Section: Discussionmentioning
confidence: 99%
“…METTL3 is the master component of the writer complex and plays key roles in regulating gene expression [ 32 ]. METTL3 was reported to display a dual role as both an oncogene and a tumor suppressor [ 39 ]. Previous publications have reported that METTL3 is downregulated in PTC and functions as a suppressor by regulating neutrophil infiltration, which was in line with our observations [ 26 ].…”
Section: Discussionmentioning
confidence: 99%